Optimal policy for behavioral financial crises - Fontanier, Paul (Journal of Financial Economics, 2025)
Should policymakers adapt their macroprudential and monetary policies when the financial sector is vulnerable to belief-driven boom-bust cycles? I develop a model in which financial intermediaries are subject to collateral constraints, and that features a general class of deviations from rational expectations. I show that distinguishing between the drivers of behavioral biases matters for the precise calibration of policy: when biases are a function of equilibrium asset prices, as in return extrapolation, new externalities arise, even in models that do not have any room for policy in their rational benchmark. These effects are robust to the degree of sophistication of agents regarding their future biases. I show how time-varying leverage, investment and price regulations can achieve constrained efficiency. Importantly, greater uncertainty about the extent of behavioral biases in financial markets reinforces incentives for preventive action.